Fikih Harmoni Syekh Wasil: Integrasi Nalar Humanitarian dan Maqasid Al-Shari’ah Jasser Auda di Kediri - Solikhudin, Muhammad; Syamsuri, Syamsuri; Khazin, A Mufti; Musadad, Ahmad; Nahidloh, Shofiyun; Hatta, Moh.; Pujiati, Tri (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2025)
Interreligious relations require wisdom to foster social harmony. Interfaith dialogue is an essential effort in achieving this goal. This study extends previous discourses by elaborating on the concept of fiqh al-harmony (jurisprudence of harmony) as developed by Shaykh Wasil, analyzed through Jasser Auda’s framework of maqāṣid al-sharī‘ah. Employing a qualitative, library-based method with both conceptual and historical approaches, this research explores the contributions of Shaykh Wasil, a 12th-century Persian scholar who came to Kediri at the invitation of King Jayabaya. Through his work Musarar, he promoted Islam using a harmony-based approach. When analyzed through Auda’s six features of maqāṣid al-sharī‘ah, Shaykh Wasil’s jurisprudence of harmony reveals significant relevance: cognitive nature classifies it within political jurisprudence (fiqh al-siyāsah); wholeness emphasizes conflict resolution through a comprehensive framework; openness integrates jurisprudence with Sufism, positive law, and the sociology of law; interrelated hierarchy identifies his harmonious da‘wah strategy as a manifestation of both maqāṣid al-ummah and maqāṣid al-insāniyyah; multi-dimensionality fosters common ground in interreligious conflict; and purposefulness demonstrates that his ultimate aim was to promote Islam as a mercy for all creation. This model of fiqh emphasizes tolerance, honesty, and rationality as essential dimensions of religious life.Keywords: Jurisprudence of harmony; Jasser Auda; Maqāṣid al-sharī‘ah; Shaykh Wasil; Religious tolerance